Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/s13762-019-02446-9
|View full text |Cite
|
Sign up to set email alerts
|

Sorption behavior of methylene blue from aqueous solution by raphia fibers

Abstract: This research shows a method of elimination of methylene blue from aqueous solutions using raphia fiber. Sorption was applied in a bath system and in the system with mixing and online measurement. The obtained data in equilibrium can suggest adjusting the sorption isotherm model and calculation of the maximum sorption capacities. The Langmuir isotherm model has the highest correlation coefficient R 2 which shows that the adsorption process of methylene blue on the raphia fibers is a monolayer adsorption proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Some studies on adsorbing performance of various materials for the studied dyes and the corresponding maximum adsorption capacities have been reported [ 25 , 26 , 33 , 36 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], which are listed in Table 4 . Compared with referred materials, the mesoporous carbons obtained by impregnation of well-organized silicas proved to be similar or even more efficient adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies on adsorbing performance of various materials for the studied dyes and the corresponding maximum adsorption capacities have been reported [ 25 , 26 , 33 , 36 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ], which are listed in Table 4 . Compared with referred materials, the mesoporous carbons obtained by impregnation of well-organized silicas proved to be similar or even more efficient adsorbents.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the adsorption isotherms, the experimental data were analyzed by using three experience isothermal adsorption models, including the Freundlich isothermal adsorption model [ 37 ], the Langmuir isothermal adsorption model [ 38 ], and the Temkin isothermal adsorption model [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The pseudo-second-order model is based on the assumption that the chemisorption is the rate-limiting step during the adsorption process [ 39 ]. The low values of the rate constant ( k 2 ) in the pseudo-second-order model suggested that the adsorption rate was primarily affected by the number of unoccupied functional groups on the adsorbent and the rate of adsorption decreased with the increasing contact time [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%